Humanized nursing assistance to premature newborns (Brazilian Journal of Health Research, 2019)
Introduction:The humanization movement in children inpatient units has increased in recent years, based on the understanding that neonates come from a family nucleus that falls ill together with their newborn. Objective: Analyzing Brazilian scientific studies about humanized care provided by nurses to premature newborns. Methods: Literature review applied to studies published in the Scientific Electronic Library Online and Virtual Health Library databases, from 2008 to 2018. Monographs, theses, dissertations and articles published in duplicate in these database were excluded from the study. Initially, 86 studies were identified based on the selected descriptors. Results: Ten publications were selected and subjected to content analysis. Although nurses understand the importance of providing humanized care, it does not effectively happen due to several activities performed by them. However, nurses prioritize single care provided to newborns, who face imminent risk of death, and leave their families to deal with their anxieties and fears; however, this lack of support often leads them to have controversial ideas about the health condition of the neonate. Conclusion: The humanized care provided by nurses to premature newborns is of paramount importance, since their hospitalization disrupts family dynamics beyond the emotional aspect. Humanized health care assistance faces several challenges, which are mainly associated with the resistance of some professionals to approach patients’ family and with lack of adequate physical structure.